2021
DOI: 10.1016/j.ultsonch.2021.105664
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ultrasonic parameters on the exfoliation of NiFe LDH nanosheets as electrocatalysts for the oxygen evolution reaction in alkaline media

Abstract: Highlights The influence of parameters on ultrasonic exfoliation of the NiFe LDH in pure water was studied. Various Concentration, amplitude, sonication times were investigated for exfoliation. The optimum condition of ultrasonic exfoliation of 60%, 10 mg mL −1 and 15 min. The best OER activity shows 250 mV overpotential at a current density of 10 mA cm −1. Enriche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…Stepped thickening of Pt–LDH/CeO 2 consolidates that the structure of the catalyst is CeO 2 -capsuled inside the skeleton of CoAl–LDH, consistent with the results of ACTEM. The images prove that the LDHs were exfoliated successfully. , Because of the lamellar structure of LDH, the crystal growth may lead to the enlarged size of the sheet when the metal ions were nucleated on CeO 2 . The new nucleated site may need high energy than the crystal growth, leading to the dispersed LDH dots on the LDH sheet.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…Stepped thickening of Pt–LDH/CeO 2 consolidates that the structure of the catalyst is CeO 2 -capsuled inside the skeleton of CoAl–LDH, consistent with the results of ACTEM. The images prove that the LDHs were exfoliated successfully. , Because of the lamellar structure of LDH, the crystal growth may lead to the enlarged size of the sheet when the metal ions were nucleated on CeO 2 . The new nucleated site may need high energy than the crystal growth, leading to the dispersed LDH dots on the LDH sheet.…”
Section: Resultsmentioning
confidence: 75%
“…The images prove that the LDHs were exfoliated successfully. 29,30 Because of the lamellar structure of LDH, the crystal growth may lead to the enlarged size of the sheet when the metal ions were nucleated on CeO 2 . The new nucleated site may need high energy than the crystal growth, leading to the dispersed LDH dots on the LDH sheet.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 99%
“…In general, the traditional LDHs are layered stacked structures, which not only shield a large number of catalytic active sites, but also inhibit the electron and mass transfer during electrocatalytic reactions over the catalyst. Therefore, it can be stripped into ultrathin nanosheets with smaller sizes by the exfoliation strategy to significantly enhance electrocatalytic performance [ 125 , 126 , 127 , 128 , 129 ]. The peeled single-layer ultra-thin LDHs nanosheets provide a large surface area and more electrochemically active sites, thus facilitating the reaction with reactants.…”
Section: Morphological Strategymentioning
confidence: 99%
“…Additionally, the ultrasonic treatment is one of the indispensable methods to peel off 2D layered materials. Zheng et al explored the effect of exfoliating NiFe-LDH on the performance of the catalyst OER under different ultrasonic conditions (including suspension concentration, sonification times, and amplification in water) [ 127 ]. TEM images showed that the stacked NiFe-LDH nanolayers were peeled off into ultra-thin layered structures, and the thickness could even reach 0.227 nm ( Figure 15 k,l).…”
Section: Morphological Strategymentioning
confidence: 99%
“…Similarly, various nickel-iron combinations have shown promising results for OER catalysis. 32,33 These studies have indicated that the catalyst fabrication process, morphology and support material are the important parameters which contribute towards higher efficiency of the OER. It has been observed that previous OER studies based on the NiFe electrocatalyst used nano powders, which certainly require some polymer binders (like Naon) for better adhesion with the current collector.…”
Section: Introductionmentioning
confidence: 99%